Case report: Use of therapeutic drug monitoring and pharmacogenetic testing as opportunities to individualize care in a case of flecainide toxicity after fetal supraventricular tachycardia - Palmen, Ronald; Sandritter, Tracy; Malloy-Walton, Lindsey; Follansbee, Christopher; Wagner, Jonathan B. (Frontiers in Pediatrics, 2023)
Flecainide is a class IC anti-arrhythmic utilized as prophylaxis of refractory paroxysmal supraventricular tachycardias in pediatric populations. Despite being a highly effective agent, its narrow therapeutic index increases the risk of toxicity and proarrhythmic events, including wide-complex tachycardia. In the absence of direct plasma sampling in the fetus to quantitate flecainide systemic concentrations, clinicians typically make drug dosing decisions from maternal plasma concentrations and QRS duration on maternal ECGs. There remains a paucity of standard guidelines and data to inform the timing and frequency of the aforementioned test in pregnancy and timing of flecainide discontinuation prior to childbirth. Flecainide primarily undergoes metabolism via cytochrome P450 (CYP). Given the variance of CYP-mediated metabolism at the level of the individual patient, pharmacogenomics can be considered in the patient that presents with flecainide toxicity to determine the maternal versus fetal factors as an etiology for the event. Lastly, pharmacogenetic testing can be utilized as an adjunct to guide flecainide dosing decisions, but must be done in caution with the neonate < 2 weeks of age. This case report highlights utilization of pharmacogenomic testing and therapeutic drug monitoring as adjuncts to guide therapy for a newborn with refractory supraventricular tachycardia, who experienced flecainide toxicity immediately post-partum and was trialed unsuccessfully on multiple alternative antiarrhythmics without rhythm control.